MCSD : designing & implementing web sites using Microsoft FrontPage 98 - Karlins, David (Upper Saddle River, N.J. : Prentice Hall PTR, 2000)
BASIC APPROACH PLEASE PROVIDE COURSE INFORMATION.
Includes bibliographical references and index.
Keywords: Web sites -- Study guides -- Design -- Examinations; Electronic data processing personnel -- Certification; Microsoft software -- Examinations -- Study guides